Liebe und Ehe: Lehrgedichte von dem Stricker (Online access: OAPEN DOAB Directory of Open Access Books., 1970)
With der Stricker, an early representative of the post-courtly period, dawns the beginning of a new attitude towards love and marriage. Poems by the itinerant poet revealing these concepts form the basis of this work. An informative introduction encompassing a detailed bibliography focuses on editing principles, the genre of the bispel, and the poet's ideals of love and marriage. The commentary lists variants of the Middle High German, and features glosses of difficult words and passages.